2021
DOI: 10.1101/gr.262055.120
|View full text |Cite
|
Sign up to set email alerts
|

Improved redox homeostasis owing to the up-regulation of one-carbon metabolism and related pathways is crucial for yeast heterosis at high temperature

Abstract: Heterosis or hybrid vigor is a common phenomenon in plants and animals; however, the molecular mechanisms underlying heterosis remain elusive, despite extensive studies on the phenomenon for more than a century. Here we constructed a large collection of F1 hybrids of Saccharomyces cerevisiae by spore-to-spore mating between homozygous wild strains of the species with different genetic distances and compared growth performance of the F1 hybrids with their parents. We found that heterosis was prevalent in the F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 99 publications
(184 reference statements)
0
8
1
Order By: Relevance
“…However, in our opinion, this phenomenon needs to be confirmed. In contrast to our recent study (Song et al, 2021), Bernardes et al (2017) did not observe significant heterosis in intraspecific hybrids of S. cerevisiae either.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in our opinion, this phenomenon needs to be confirmed. In contrast to our recent study (Song et al, 2021), Bernardes et al (2017) did not observe significant heterosis in intraspecific hybrids of S. cerevisiae either.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, oxidative modifications can occur on ribosomal proteins and ribosome modifying enzymes which may interfere with translation (Shcherbik & Pestov, 2019 ). NADPH production could also attenuate errors in protein synthesis by reducing the abundance of free radicals that would otherwise cause expression of genes associated with DNA damage, oxidized mRNA, and proteolysis (Song et al, 2021 ). Altogether, increasing NADPH to reduce oxidative stress could allow for the high rate of protein synthesis that occurs during MOV and suggests that modulating NADPH could lead to improvements in protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous yeast cells are usually more vigorous than homozygous cells in growth and stress tolerance because of heterosis, or hybrid vigor [ 41 , 93 , 94 , 95 , 96 , 97 ]. Recently, Song et al [ 98 ] showed that thermotolerant heterosis is prevalent in the F1 hybrids formed by spore-to-spore mating of different wild S. cerevisiae strains. The hybrids can usually cope with oxidative stress more effectively by up-regulation of their one-carbon metabolism and related pathways, leading to reduced DNA and protein damage and higher energy use efficiency.…”
Section: Intrinsically Different Life Strategies Of the Wild And Dome...mentioning
confidence: 99%
“…Tolerance to high osmolarity, temperature, ethanol concentration, and ROS level is required for domesticated strains [ 92 ]. A recent study showed that heterosis contributes to high-temperature tolerance of domesticated S. cerevisiae [ 98 ], while another study showed that artificial hybrids of S. paradoxus did not show heterosis [ 129 ], implying heterozygosity may not contribute to the fitness of this species. Indeed, heterozygous strains of S. paradoxus and other non- cerevisiae Saccharomyces species have rarely been found in nature or man-made environments, though inter-species hybrids of Saccharomyces species are not uncommon in industrial yeast strains [ 101 , 128 , 130 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%